THE PHYSIOLOGICAL RESPONSE OF LAYING QUAILS TO NATURAL AND ARTIFICIAL LIGHT INTENSITY - Ashwaq. A. Hassan,; Hadeel. M. Hameed,; Hiyam N. Maty, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The current study was aimed to investigate the impact of white light of various intensity of illumination on some reproductive and hematological parameters of female quail (Coturnix coturnix), Where 80 one-day-old birds were used, separated into four groups distributed as follows: The 1st  represented as control was exposed to natural lighting, while 2ed ,3rd ,4th  was subjected to different intensity of light represented by 0.6, 25 and 45 lux, respectively, for 5 h/day, each group was divided into 4 replicates. The study continued for 8 weeks. The results indicates a notable raise in the level of FSH and LH hormone with an increase in ovarian weight, an elevate in the number of outgrowth and grown-up follicles for groups exposed to 25 and 45 lux light intensity compared to control and 0.6 lux. It was observed for the same groups an increases in the weight of the edible organs (heart, liver and gizzard). In addition, there was a clear increase in the number of RBC, WBC, lymphocytes, hemoglobin and PCV levels, while the 25 and 45 lux groups showed a decline in the level of MCV with a raise in MCH and MCHC compared with the control and 0.6 lux. It conclude that the intensity of different lighting had positive effects in improving some reproductive and blood characteristics of female quail.